Precarious Employment in Academia: Unpacking the Dominance of Job Satisfaction Over Organizational Commitment in Predicting Turnover Intention - Alfian Noor; Meiske Claudia (Open Access Indonesia Journal of Social Sciences, 2025)
Precarious employment is an increasingly prevalent feature of the academic landscape, particularly within Indonesian higher education institutions, posing significant challenges for human resource management. This study investigated the complex interplay between job satisfaction, organizational commitment, and turnover intention among non-permanent (contractual) employees at Universitas Lambung Mangkurat (ULM), a context characterized by employment uncertainty. A quantitative, descriptive-analytical survey design was employed. Data were collected via questionnaires from a proportionally stratified sample of 128 non-permanent employees at ULM. Structural Equation Modeling with Partial Least Squares (PLS-SEM) was utilized to test the hypothesized relationships between job satisfaction, organizational commitment (affective, continuance, and normative), and turnover intention. The findings revealed that job satisfaction had a significant positive influence on organizational commitment (β=0.422, p<0.001) and a significant negative influence on turnover intention (β=-0.371, p=0.013) among non-permanent academic staff. However, contrary to some established models, organizational commitment did not demonstrate a statistically significant direct effect on turnover intention (β=-0.216, p=0.108). Furthermore, organizational commitment did not significantly mediate the relationship between job satisfaction and turnover intention in this cohort (β=-0.091, p=0.260). In conclusion, job satisfaction emerged as a more dominant predictor of turnover intention than organizational commitment. The inherent uncertainties and limited long-term prospects associated with non-permanent contractual roles appear to diminish the capacity of organizational commitment to retain employees or mediate the effects of job satisfaction. These findings underscore the critical need for higher education institutions to prioritize enhancing job satisfaction for their precariously employed staff as a primary retention strategy.